2020
DOI: 10.1111/cdoe.12602
|View full text |Cite
|
Sign up to set email alerts
|

Diet and root surface caries in a cohort of older Japanese

Abstract: Objectives Root surface caries experience tends to increase with age. The purpose of this longitudinal study was to evaluate the relationship between aspects of dietary intake, including milk and sucrose in coffee or tea (SCT), and root surface caries in older Japanese individuals. Methods 303 community‐dwelling older individuals (age 75 years) were enrolled for analysis. All participants underwent a dental examination at baseline and then annually from 2003 to 2008 (ie six times over a 5‐year period). A disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…Decreased immune function in older people may lead to a reduced capability to suppress the cariogenic activity of oral flora and, consequently, rapid tooth destruction. Dietary factors such as sucrose [9] and milk [6] intake have also been associated with root caries incidence. However, because some of our subjects were living in their OHs, complete information regarding their diet could not be collected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased immune function in older people may lead to a reduced capability to suppress the cariogenic activity of oral flora and, consequently, rapid tooth destruction. Dietary factors such as sucrose [9] and milk [6] intake have also been associated with root caries incidence. However, because some of our subjects were living in their OHs, complete information regarding their diet could not be collected.…”
Section: Discussionmentioning
confidence: 99%
“…Local (intraoral) risk factors for root caries incidence include the presence of two or more full-coverage restorations [5], poor oral hygiene [5,7], high amounts (>10 5 CFU/mL) of salivary lactobacilli [5], and mean attachment loss > 3.6 mm [5]. Systemic risk factors for root caries include serum albumin levels < 4.0 g/dL [8], low milk and dairy product intake [6], high sucrose intake [9], and low body mass index (BMI) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Older adults experience a decline in taste perception of salty, sweet, and umami with age and tend to choose stronger flavours, with a greater consumption of sweet and salty foods [ 25 ], which may increase sugar intake. A study showed that intake of sucrose in coffee or tea was associated with the increment of root surface caries in community-dwelling older Japanese adults [ 26 ].…”
Section: The Impact Of Diet and Nutrition On Oral Healthmentioning
confidence: 99%
“…Tooth loss has been studied for decades and there are many different causes attributed to it, such as dental decay, periodontal disease, and trauma [ 1 ]. Dental caries and periodontal disease are known to be related to social and behavioural factors [ 1 ] and diet [ 2 ]. The lack of access to dental care [ 3 ], tobacco use [ 1 ], and poor oral health knowledge and oral hygiene practices [ 4 ] also play a crucial role in the progression of these oral conditions.…”
Section: Introductionmentioning
confidence: 99%